Long-duration GPS record from Rutford Ice Stream, West Antarctica, 2004-2007 - Smith, Andrew; Murray, Tavi; King, Matt (UK Polar Data Centre, Natural Environment Research Council, UK Research & Innovation, 2020)
Dual-frequency GPS data from a single receiver installed on the surface of Rutford Ice Stream in West Antarctica. The instrument was operated from late 2004 to early 2007. Gaps in the data set occur, through periods of power loss in the winters and during station relocations. Funding was provided by NERC Antarctic Funding Initiative (AFI) GR3/G005, NERC under the British Antarctic Survey National Capability programme, Polar Science for Planet Earth, Leverhulme Trust Fellowship (to T Murray), and RCUK Academic Fellowship (to M A King). : GPS position observations were made at 0.1 Hz sample rate using a Trimble 5700 dual-frequency receiver with tripod-mounted antenna. The ice stream at the measurement site is moving at just over 1 m per day (377 m/a). Prior to each Antarctic winter, the instrument was re-located, usually to approximately its original geographical (latitude, longitude) position. During data processing, the antenna position was calculated every 5 minutes using a Precise Point Positioning technique. For further details see Murray et. al, 2007 (doi:10.1029/2007GL031207) and King et. al, 2010 (doi:10.3189/002214310791190848). : GPS data were acquired using a Trimble 5700 dual-frequency receiver with tripod-mounted antenna. Data start date is 17 December 2004 (2004 Decimal Day 353.778). The data span a period of 750 days (to decimal day 2004 1103.997). Gaps exist in the time series through periods of power loss in the winters and during station relocations The data were acquired at one site on Rutford Ice Stream, West Antarctica. Approximate location of the site was S78.141646342 W088.91234181 in Dec 2004. Ice flow is ~377 m per year. Station relocations were up to a few hundred metres each time. : Position errors (95% confidence limits) are 0.02-0.03 m (horizontal) and 0.05 m (vertical). For details see Murray et. al, 2007 (doi:10.1029/2007GL031207) and King et. al, 2010 (doi:10.3189/002214310791190848). Gaps exist in the time series through periods of power loss in the winters and during station relocations.